2007
DOI: 10.1097/mao.0b013e318159e76a
|View full text |Cite
|
Sign up to set email alerts
|

Revision Surgery for Residual or Recurrent Vestibular Schwannoma

Abstract: Most residual tumors after primary surgery are successfully managed with watch and rescan. Tumor fragment size is the greatest determinant of revision treatment. After revision surgery, tumor regrowth is much less predictable. Revision surgery is usually considerably more difficult than primary surgery, with a higher complication rate, particularly with regard to the facial nerve. Changing the approach for revision surgery may confer an advantage to facial nerve function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
32
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 19 publications
(16 reference statements)
1
32
1
Order By: Relevance
“…3 In this series, several patients experienced moderate temporary postoperative facial nerve weakness. These patients recovered function after a period of time, but it is useful to note that there was a tempo- rary problem, possibly a result of intraoperative irritation of the facial nerve.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…3 In this series, several patients experienced moderate temporary postoperative facial nerve weakness. These patients recovered function after a period of time, but it is useful to note that there was a tempo- rary problem, possibly a result of intraoperative irritation of the facial nerve.…”
Section: Discussionmentioning
confidence: 99%
“…This is only slightly higher than the risk of regrowth for more complete resection, and not nearly as high as the risk of recurrence with other STR strategies. 3 All patients who later had regrowth of their tumors had initially been treated with a subtotal microsurgical resection. None of the patients treated with GTR required retreatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such patients tended to have worse outcomes, both before and after SRS. Freeman et al found that 8 (30%) of 27 patients who underwent 1 repeat resection underwent additional treatment for tumor progression, 10 indicating a tumor control rate after repeat resection of 70%.…”
Section: Discussionmentioning
confidence: 99%